Pelatihan Batik Shibori sebagai Upaya Pengembangan Kreativitas Siswa MI Muhammadiyah 07 Sungegeneng Lamongan - Farahana Zahro Aini; Fairuz Addailamy; Abduh Lutfan; Arul Afdiansyah (SEWAGATI: Jurnal Pengabdian kepada Masyarakat, 2026)
Cultural preservation is an important aspect that needs to be instilled from an early age. However, the condition at MI Muhammadiyah 07 Sungegeneng indicates limited student access to various forms of local cultural arts, where previous art activities were only confined to basic drawing and coloring. To address this issue, KKN Universitas Billfath Lamongan conducted Batik Shibori training to introduce the tie-dye technique, foster creativity, and promote character values such as cooperation, discipline, and responsibility. The training followed a systematic approach: material delivery, technical demonstration, hands-on practice, and evaluation. Involving 18 students divided into small groups, the activity saw high enthusiasm as participants actively folded, tied, and dyed fabric to create unique motifs like flowers and ornaments. The results indicate that the activity improved students’ technical understanding and artistic skills. Therefore, shibori batik can be considered an effective, engaging, and educational medium for cultural preservation and character development in elementary education.